2023
DOI: 10.1186/s12967-023-04157-9
|View full text |Cite
|
Sign up to set email alerts
|

The oncogenic role of NF1 in gallbladder cancer through regulation of YAP1 stability by direct interaction with YAP1

Abstract: Background Gallbladder cancer (GBC) is the most prevalent and invasive biliary tract malignancy. As a GTPase-activating protein, Neurofibromin 1 (NF1) is a tumor suppressor that negatively regulates the RAS signaling pathway, and its abnormality leads to neurofibromatosis type 1 (NF-1) disease. However, the role of NF1 playing in GBC and the underlying molecular mechanism has not been defined yet. Methods A combination of NOZ and EH-GB1 cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
3
1
Order By: Relevance
“…Interestingly, YAP promotes the proliferation of GBC, [ 14 ] but we did not find any influence of DNMT3A on GBC growth. YAP and TAZ are the key downstream effectors of the Hippo pathway.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Interestingly, YAP promotes the proliferation of GBC, [ 14 ] but we did not find any influence of DNMT3A on GBC growth. YAP and TAZ are the key downstream effectors of the Hippo pathway.…”
Section: Discussioncontrasting
confidence: 73%
“…Although YAP/TAZ is required for metastasis in various solid tumors, [ 13 ] and the oncogenic role of YAP in the tumor growth of GBC has been confirmed, [ 14 ] the biological function of YAP/TAZ in driving GBC metastasis remains uncertain. We verified the biological validity of YAP/TAZ in GBC metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, recent studies have demonstrated a close link between autophagy and Yes‐associated protein 1 (YAP1)‐WWTR1/ transcriptional coactivator with PDZ‐binding motif (TAZ) signalling. The carcinogenicity of YAP1/TAZ has been confirmed in many cancers 19–21 . After autophagy inhibition/induction, YAP1 /TAZ signalling increases or decreases owing to the regulation of CTNNA1/alpha‐catenin levels 22 .…”
Section: Introductionmentioning
confidence: 98%
“…The carcinogenicity of YAP1/TAZ has been confirmed in many cancers. 19 , 20 , 21 After autophagy inhibition/induction, YAP1 /TAZ signalling increases or decreases owing to the regulation of CTNNA1/alpha‐catenin levels. 22 In YAP1‐mutated phagocytic cells, the autophagic process was suppressed because of decreased YAP1‐TEAD transcriptional activity during Staphylococcus aureus infection.…”
Section: Introductionmentioning
confidence: 99%